Significance of heat conduction in binary reactive flow of Walter’s B fluid with radiative flux and activation energy - Alzahrani, Faris; Khan, M. Ijaz (Modern physics letters. B, Condensed matter physics, statistical physics, applied physics, 2021)
The prime objective of binary chemical reaction (BCR) is concentrated on the study and optimization of chemical reaction to accomplish finest reactor design and performance, which elaborated the interfaces of flow phenomena, reaction kinetics and heat and mass transport. The reactor performance is likely to be linked to the reaction operating constraints and feed composition through the aforementioned factors. The applications of BCR are generally in the petroleum and petrochemical regions, but with the help of chemical engineering and reaction chemistry concepts, it could be used in different areas, like waste treatment, chemical pharmaceuticals, nanoparticles in advanced materials, microelectronics, enzyme technology, biochemical engineering, living systems, renewable energy systems, sustainable development, environment/pollution prevention, as well as to optimize a different reaction framework via simulation and modeling methodology. Owing such physical applications in mind, this research deals with the binary chemical reactive flow of non-Newtonian fluid (Walter’s B) subject to activation energy. Stagnation point is accounted. Radiative flux and ohmic heating effects are considered in the development of energy expression. Concentration and microorganism equations are considered. The governing system is altered to ordinary one through the important similarity variables. Results are obtained through bvp4c technique. All results are discussed graphically. Furthermore, surface drag force (skin friction) and heat and mass transfer (Nusselt and Sherwood) rates are calculated and displayed graphically. Significant results are listed in conclusion.